Enhancement of Oral Production through the Teaching of Culture in Content-Based Instruction - Montero Chacón, Tatiana Vanessa (2016)
This present study explores the practice of enhancing oral production by teaching culture within a Content-Based Instruction approach, and it was done at the Centro de Estudios en Inglés Conversacional (CEIC), an outreach program from Universidad Nacional (UNA) with a group of intermediate English as Foreign Language students. The aim of this study was to determine whether the students enriched their oral production from including cultural topics into communicative tasks. As a main finding, the participants enhanced their oral performance, focusing on content rather than on the language forms; likewise, the participants efficiently incorporated cultural content into their oral production.